216k views
1 vote
If f(x)= (2x)^2, how do I find f(-4)? Explain.

User Onyeka
by
5.0k points

2 Answers

3 votes

Answer:

the answer is 64

Explanation:

f(-4) means that x is -4 (in other words it replaces x)

so thatll be f(-4) = (2(-4))^2

solve by PEMDAS (Parenthesis, Exponent, Multiplication, Division, Addtion Subtraction)

meaning 2 times -4 equals -8

-8 raised to the second power is saying -8 times -8 which equals 64

User Guilford
by
4.8k points
1 vote

Answer:

64

Explanation:

f(4-)=2(-4)^2

2*-4=-8

-8^2=64

User NielMalhotra
by
4.9k points